(3OdGFd GdfHhIs - (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3Chd HGH ajg eG hQO HGH GYJQGV ef GYJV ef Cgd GdfaGb s
(3Ydjg SeGYGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B134 s
Keywords: (3GdJGQjNs